THE INVESTIGATION OF AFFIXES IN PREMIS JOURNAL OF ENGLISH STUDY PROGRAM AT MUHAMMADIYAH UNIVERSITY OF METRO - Palupi K2, Fitri; Latif D, Syaifudin; Dwi Antika, Riris (Lingustic, Literature and English Education, 2021)
Morphology is a branch of linguistics that identifies basic units of language as grammatical units. Morphology is the basic of the word because from morphologi the word is formed. In morphology there are two ways to identify, the morphological process and morphological analysis. The aims of this research are to find out the types of affixes and to reveal are the most dominant of using affixes in Journal Premis of English Study Program, Muhammadiyah University of Metro. The object of this research is the affixation that used in The Premis Journal of English Study Program, Muhammadiyah University of Metro. The subject of this research is Premis Journal of English Study Program, Muhammadiyah University of Metro. Descriptive qualitative research is a method of this research. In this research found are 1.171 affixation, consist of prefix are 52 d ata, suffix are 343 data and inflectional morpheme 776. The most dominant types of using affixation in this data is inflectional morpheme with the percentage 66%. Based on the data it can be concluded that in the Journal found all of the affixation with different grade.